Assessing COVID-19 Lockdown's Impact: Domestic Violence Against Women in a Selected community of Lalitpur - KC, Reshma; KC, Smriti; Poudel, Saroja (Academia Research Journal, 2024)
This study examines at how prevalent domestic violence was against women in a particular Lalitpur community during the Covid-19 lockdown. Violence against women encompasses acts of aggression directed primarily or exclusively towards women and girls. The confluence of economic strain, movement restrictions, heightened partner frustration, and the disruption of social and protective networks during the lockdown amplifies women's susceptibility to exploitation and abuse. Employing a descriptive cross-sectional design, the study employed a convenient sampling technique to select 74 married women within the reproductive age group. A systematic interview schedule was used for data collection, and inferential statistics like the Chi-square test were used in conjunction with descriptive statistics like frequency and percentage for the analysis that followed. The study found that during the Covid-19 shutdown, domestic violence against women was prevalent in 31.1% of cases. Victims reported experiencing emotional (37.7%), economic (23.0%), physical (31.1%), and sexual (8.2%) violence. The primary contributing factors to the occurrence of violence were identified as being confined at home with the abuser (31.1%), financial concerns (28.4%), and problematic inter-relationships within family members (28.4%). Of the variables taken into account, the only ones that showed a significant correlation with the occurrence of domestic violence during the Covid-19 lockdown era were the husband's employment, education, and history of violence. The results highlight how urgent it is to address domestic abuse of women in Nepal, especially during times of crisis like the Covid-19 lockdown. It is imperative for the country to prioritize the enhancement of support systems to prevent the occurrence of such violence and safeguard the well-being of victims.